MAGNETIC PROPERTIES OF HEMATITE NANOSTRUCTURES - Munayco S., J. (2010)
Nanostructured a-Fe203 (hematite) was produced usíng high-energy ball milling and analized by X-ray diffraction (XRD), 57Fe Mi.issbauer spectrometry and magnetization measurements. The results showed that after 2 h milling, a-Fe203 nanosize particles were obtained about 15 nm. The 57 Fe Mossbauer spectrometry correlated with magnetometry showed also that Morin transition was notobserved after 0,75 h milling.